Perlindungаn Hukum Hak Pekerja Atas Keselamatan Kerja : Studi Di Kаwаsаn Wilаyаh Industri Petis Kecаmаtаn Muncаr Kаbupаten Bаnyuwаngi - Redyana Lutfianidha (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
Muncar District, Banyuwangi Regency is one of the districts which is an industrial area, especially in the field of processed marine products, such as petis, sardines and and others. There are also quite a lot of workers at UD in Muncar sub-district. The author is interested in conducting research at UD which is engaged in petis processing in Muncar District. The UDs referred to in this research are UD Dewi Sri Ayu, UD Kurnia Industri, and UD Tiga Bawang Putih. Petis companies in Muncar sub-district, Banyuwangi district are very vulnerable to work accidents. This is because to produce petis, high power machines are used and very sharp knives are used to cut fish and also to crush shrimp heads which are used as raw materials for making petis. K3 safety in carrying out this work is very important because considering the situation and conditions faced in the work environment, it is very prone to work accidents. Likewise, what happened at UD Kurnia Industri, the atmosphere and conditions were very uncomfortable because the production system carried out was not in accordance with standards, one of which was that there was no dampening of air pollution and heat because the tools used to cook petis were still very simple and traditional.